2016
DOI: 10.20490/roavs/16-023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Olibanum (Boswellia thurifera) as a feed additive on performance, some blood biochemical and intestinal morphology in broiler chicks

Abstract: To determine the effect of Olibanum on performance, some blood biochemical and intestinal morphology of broiler chicks, a total 360 one day Ross 308 broiler chicks were divided into 6 dietary treatments. The chicks were fed a basal diet as control; basal diet with 0.01% (T1), 0.015% (T2), 0.02% (T3), 0.03% (T4) and 0.05% (T5) of Olibanum. No significant difference was found in feed intake, weight gain and feed conversion ratio between the control and treated groups. Serum triglyceride level decreased significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…These compounds are responsible for anti-inflammatory, antiseptic, analgesic, antibacterial, anticancer, hepatoprotective, hypolipidemic, hypocholesterolemic, immunomodulatory, and antiproliferative effects in vitro and in vivo [7][8][9][10][11][12][13]. The supplementation of this phytoextract in broiler diets improves the breeding performance and the digestibility of nutrients due to the microbiological stabilisation of the small intestine by the activity of boswellic acids [14,15]. Moreover, some studies have reported the hypolipidemic effects of Bs and an improvement in the quality of poultry meat [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are responsible for anti-inflammatory, antiseptic, analgesic, antibacterial, anticancer, hepatoprotective, hypolipidemic, hypocholesterolemic, immunomodulatory, and antiproliferative effects in vitro and in vivo [7][8][9][10][11][12][13]. The supplementation of this phytoextract in broiler diets improves the breeding performance and the digestibility of nutrients due to the microbiological stabilisation of the small intestine by the activity of boswellic acids [14,15]. Moreover, some studies have reported the hypolipidemic effects of Bs and an improvement in the quality of poultry meat [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Phytobiotics, also known as phytogens, are less toxic, residue-free and growth-boosting feed additives. They alter gut microorganisms, improve digestibility and performance, improve intestinal architecture and stimulate intestinal mucus secretion (Alloui et al, 2014); (Tabatabaei, 2016). These benefits include enhanced nutrient absorption, digestion, growth enhancement, immune modulation and gut health, ultimately improving the safety of poultry products (Rafiq, 2021).…”
Section: Introductionmentioning
confidence: 99%